Keratin 8 phosphorylation regulates keratin reorganization and migration of epithelial tumor cells - Busche, Tobias; Spatz, Joachim P. (Journal of cell science, 2012)
Skip to Next Section Cell migration and invasion are largely dependent on the complex organization of the various cytoskeletal components. Whereas the role of actin filaments and microtubules in cell motility is well established, the role of intermediate filaments in this process is incompletely understood. Organization and structure of the keratin cytoskeleton, which consists of heteropolymers of at least one type 1 and one type 2 intermediate filament, are in part regulated by post-translational modifications. In particular, phosphorylation events influence the properties of the keratin network. Sphingosylphosphorylcholine (SPC) is a bioactive lipid with the exceptional ability to change the organization of the keratin cytoskeleton, leading to reorganization of keratin filaments, increased elasticity, and subsequently increased migration of epithelial tumor cells. Here we investigate the signaling pathways that mediate SPC-induced keratin reorganization and the role of keratin phosphorylation in this process. We establish that the MEK-ERK signaling cascade regulates both SPC-induced keratin phosphorylation and reorganization in human pancreatic and gastric cancer cells and identify Ser431 in keratin 8 as the crucial residue whose phosphorylation is required and sufficient to induce keratin reorganization and consequently enhanced migration of human epithelial tumor cells.